Pediatric reference values for total psoas muscle area in Korean children and adolescents - Kim, Jisoo; Lee, Mi-Jung; Lim, Hyun Ji; Kwon, Yonghan; Han, Kyunghwa; Yoon, Haesung (Frontiers in Pediatrics, 2025)
BackgroundUniform cut-off values cannot be applied to children because muscle mass changes significantly with growth and different population groups have different races and lifestyles, so reference values from healthy children are needed.Materials and methodsPediatric patients (≤18 years of age) who underwent abdominal CT for abdominal pain in the emergency room without a past history from January 2015 to January 2021 were enrolled. Total psoas muscle area (tPMA) was calculated as bilateral psoas muscle areas drawn semi-automatically at the levels of L3–4 and L4–5. Graphs for weight and height were drawn and compared using data from the Korean national growth chart. tPMA distributions according to sex and age were obtained using quantile regression with smoothed polynomials. We analyzed correlations of tPMA with weight and height.ResultsA total of 740 pediatric patients were included [M:F = 340:400, 12 years (interquartile range 9–16)]. When compared to the Korean national growth chart, the 50th percentile values for height and weight in study population were not significantly different. At L3–4, the 50th percentile tPMA values ranged from 416 to 2,802 mm2 in males and 370 to 1,501 mm2 in females. The 50th percentile tPMA values for L4–5 ranged from 556 to 3,563 mm2 in males and from 579 to 2007 mm2 in females. In males, tPMA at L3–4 and L4–5 showed positive correlations with weight (r = 0.87; r = 0.87, P < 0.001, both) and height (r = 0.82; r = 0.84, P < 0.001, both). tPMA at L3–4 and L4–5 were positively correlated with weight (r = 0.77; r = 0.81, P < 0.001, both) and height (r = 0.61; r = 0.67, P < 0.001, both) in females.ConclusionWe provided sex-specific and age-specific growth charts and developed an online calculator for tPMA at the levels of L3–4 and L4–5, which can serve as an evaluation guide for muscle mass in Korean children.